The Body Shop Belanja Idealisme VS Gengsi - Setyowati, Retno Manuhoro (Jurnal The Messenger, 2016)
Identity formation is often manifested in the image of the media. These conditions are rarely noticed by individuals whose involved. Consumers are unwittingly caught up in the ever-popular culture simulakra invited into the circle of capitalism. Nowadays, to distribute beauty products, such strong idealism concepts are needed, focusing on the potential consumer, to regain their trust, by implementing pseudo-advantage values. A real example is The Body Shop products are adept at carrying the issues go green and respect for indigenous peoples. As a consumer of beauty products, women's position and then also becomes brittle by the temptations of mass media advertising for the construction of the concept of beauty has been tailored to the needs of capitalism that led to the maximum benefit.
Keywords: budaya pop; simulakra; memori jangka panjang